Knowledge Management of Phasin (Tube Skirt) Nam Ang Weaving, Uttaradit Province by Participation of Communities for Sustainable Development - Chantang, Doungrak (Journal of Fine and Applied Arts Khon Kaen University, 2024)
This research studied collecting knowledge of intangible cultural heritage and weaving knowledge management of Nam Ang community Uttaradit, and participation of the Nam Ang community Uttaradit in weaving phasin (tube skirt) network management to create sustainable development. Qualitative research was done with data collected from in-depth interviews with weavers in focus groups using semi-structured questions from the Prime Minister of Nam Ang Subdistrict Administrative Organization (NASAO). Additional data was collected from books, research papers, and related academic articles. Results were that intangible cultural heritage and community knowledge management knowledge collection consisted of 1) searching for Sin Tin Jok cloth weaving skill; 2) knowledge storage pertained to deep-seated weaving knowledge accumulated by the NASAO and recorded in writing; 3) knowledge transfer to subsequent generations of weavers permitted Nam Ang School students to learn weaving; and 4) knowledge application was used by the skill corpus; storing and exchanging knowledge; and improving operational efficiency, such as in using natural dyes. For community participation in creating network sustainability, a weaving network and community learning center were established as well as a market for selling products, producing sustainable community income.